2017
DOI: 10.1186/s12891-017-1819-3
|View full text |Cite
|
Sign up to set email alerts
|

L161982 alleviates collagen-induced arthritis in mice by increasing Treg cells and down-regulating Interleukin-17 and monocyte-chemoattractant protein-1 levels

Abstract: BackgroundTo investigate the effects and potential mechanism of L161982 (a kind of EP4 antagonist) on the collagen-induced arthritis (CIA) mice model.MethodsThe CIA mice model were first established by immunizing with Chicken Type II Collagen on DBA/1 mice. The CIA groups were administered once a day for 2 weeks with either 5 mg/kg L161982 by intraperitoneal injections (IP), 200 U celecoxib by intragastrical injections, or 100 μl PBS (IP). At the end of the study, total arthritis score and histopathologic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…On the other side, PGE 2 has also been reported to suppress Treg cell differentiation and signature gene (e.g. Foxp3, IL-10) expression from both mouse and human effector T cells through direct actions on T cells via EP2 and/or EP4 receptors [32,33,[61][62][63][64]. In agreement with these reports, blocking PG biosynthesis including PGE 2 production by NSAIDs or blocking PGE 2 signalling by an EP4 selective antagonist enhanced Foxp3 expression and iTreg induction, and therefore ameliorated T cell-mediated tissue inflammation [32,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, PGE 2 has also been reported to suppress Treg cell differentiation and signature gene (e.g. Foxp3, IL-10) expression from both mouse and human effector T cells through direct actions on T cells via EP2 and/or EP4 receptors [32,33,[61][62][63][64]. In agreement with these reports, blocking PG biosynthesis including PGE 2 production by NSAIDs or blocking PGE 2 signalling by an EP4 selective antagonist enhanced Foxp3 expression and iTreg induction, and therefore ameliorated T cell-mediated tissue inflammation [32,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3, IL-10) expression from both mouse and human effector T cells through direct actions on T cells via EP2 and/or EP4 receptors [32,33,[61][62][63][64]. In agreement with these reports, blocking PG biosynthesis including PGE 2 production by NSAIDs or blocking PGE 2 signalling by an EP4 selective antagonist enhanced Foxp3 expression and iTreg induction, and therefore ameliorated T cell-mediated tissue inflammation [32,[65][66][67]. Moreover, we have recently found that PGE 2 inhibits Treg cell expansion or accumulation in the intestine through T cell-independent but microbiotadependent mechanisms [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al ., 2010; Esaki et al ., 2010; J. Lee et al ., 2018; Robb et al ., 2017; Schiffmann et al ., 2014; Yao et al ., 2009, 2013), it has also been reported to inhibit Foxp3 induction and reduce Treg cell numbers (L. Chen et al ., 2017; H. Li et al ., 2017; Sahin & Sahin, 2020). We have recently reported a T cell-independent function of PGE 2 on facilitation of Foxp3 + Treg cell responses in the intestine (Crittenden et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2010;Esaki et al, 2010;J. Lee et al, 2018;Robb et al, 2017;Schiffmann et al, 2014;Yao et al, 2009Yao et al, , 2013, it has also been reported to inhibit Foxp3 induction and reduce Treg cell numbers (L. Chen et al, 2017;H. Li et al, 2017;Sahin & Sahin, 2020).…”
Section: Introductionmentioning
confidence: 99%